Triboelectric Touch‐Free Screen Sensor for Noncontact Gesture Recognizing - Tang, Yingjie; Zhou, Hao; Sun, Xiupeng; Diao, Ninghua; Wang, Jianbo; Zhang, Baosen; Qin, Cheng; Liang, Erjun; Mao, Yanchao (Advanced functional materials, 2020)
An intelligent human–machine interface (HMI) is a crucial medium for exchanging information between people and electronics. As one of the most important HMI devices, touch screen sensors are widely applied in personal electronics in daily life. However, as the most commonly used touch screen sensor, capacitive sensors can only detect limited kinds of gestures such as touching and sliding. Here, a triboelectric touch‐free screen sensor (TSS) is reported for recognizing diverse gestures in a noncontact operating mode by utilizing the charges naturally carried on the human body. Compared with conventional capacitive sensors, the TSS is capable of detecting various gestures such as the drop and lift of finger with different speeds, making a fist, opening palm, and flipping palm with different directions. Based on the TSS, an intelligent noncontact screen control system is further developed, which is used to unlock the smartphone interface by the noncontact operating mode. This research for the first time proposes the concept that taking the human body itself to participate in triboelectric self‐powered noncontact sensing and provides a touch‐free design concept to develop the next generation of screen sensors. It can alter the usual way that people operating their personal electronics. A triboelectric touch‐free screen sensor (TSS) for recognizing diverse gestures is successfully demonstrated. Based on the TSS, an intelligent noncontact screen control system is further developed, which realizes the unlocking of a smartphone interface via the noncontact operating mode. This TSS with the noncontact gesture sensing method could make a remarkable breakthrough in establishing intelligent human–machine interactions.